2011
DOI: 10.1159/000331501
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of In-Hospital Mortality of Patients with Hemoptysis: An Approach to Defining Severe Hemoptysis

Abstract: chanical ventilation at referral predicted independently mortality. The model showed good concordance between predicted and observed probabilities of death and good discrimination (receiver operating characteristic curve area 0.87; 95% CI 0.82-0.92). The model-based score (chronic alcoholism, pulmonary artery involvement, and radiographic patterns, 1 point each; cancer, aspergillosis, and mechanical ventilation, 2 points each) predicted the probability of death as follows: score 0, 1%; score 1, 2%; score 2, 6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 68 publications
(42 reference statements)
3
60
0
11
Order By: Relevance
“…Our results concerning in-hospital mortality (7% when deaths from lung cancer were excluded) during the first episode of haemoptysis did not differ from those in other studies [1,5,21]. The mortality rates in the subgroup of haemoptysis of unknown origin were similar, suggesting that the lack of a described aetiology at the initial evaluation was not a distinct risk factor for increased mortality in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Our results concerning in-hospital mortality (7% when deaths from lung cancer were excluded) during the first episode of haemoptysis did not differ from those in other studies [1,5,21]. The mortality rates in the subgroup of haemoptysis of unknown origin were similar, suggesting that the lack of a described aetiology at the initial evaluation was not a distinct risk factor for increased mortality in our study.…”
Section: Discussionsupporting
confidence: 53%
“…We showed that the frequency of recurrence was relatively low, since 84% of patients with initial haemoptysis had no recurrence within the 3 years of follow-up. Moreover, even though it was explored in small prospective studies, we found substantial mortality rates during the initial stay as expected [5] but, more interestingly, during the follow-up as well. Indeed, the 3-year in-hospital mortality rate, excluding lung cancers, was high at 20%.…”
Section: From the Authorssupporting
confidence: 70%
“…El riesgo de fallecer de un paciente hospitalizado por micosis y cáncer encontrado en nuestro estudio fue 0,22 y 0,25, respectivamente, Contrariamente, el riesgo de fallecer de bronquiectasia y tuberculosis activa fue 0,14 y 0,11, respectivamente. Muriet (7) en su estudio realizado en el hospital de Paris, Francia, encontró el riesgo de fallecer por micosis y cáncer de 0,08 y 0,29, respectivamente. Este riesgo bajo de mortalidad intrahospitalaria para micosis se explicaría por la baja incidencia de micosis en Francia y el bajo número de pacientes incluidos en su estudio con este diagnóstico (48/715).…”
Section: Discussionunclassified
“…Para ello sugieren que dentro de la evaluación del pronóstico del paciente con hemoptisis no solo se considere el volumen del sangrado sino que, además, se deberá tomar en cuenta otras consideraciones relacionadas fundamentalmente a la reserva respiratoria funcional del paciente (7) .…”
Section: Introductionunclassified